Reversal of anticoagulation with dabigatran in an 82-year-old patient with traumatic retroperitoneal arterial bleeding using the new antidote idarucizumab: a case report - Hofer, Stefan; Philipsenburg, Christoph; Weigand, Markus A.; Brenner, Thorsten (A&A case reports, 2016)
Dabigatran etexilate is a direct oral anticoagulant used for the prevention of stroke in atrial fibrillation. Idarucizumab is a recently approved specific antidote that reverses the effect of dabigatran within minutes. We report the case of an 82-year-old patient with traumatic retroperitoneal arterial bleeding under anticoagulation with dabigatran etexilate. By administration of idarucizumab, we successfully normalized coagulation and saved the patient from an operation. In the course of the disease, a slight reincrease in dabigatran etexilate plasma levels was observed 2 days after the reversal, which could lead to a new onset of bleeding.
Gesehen am 19.05.2020